Relationship Of Hemodialysis Frequency With Hemoglobin Levels In Patients With Chronic Renal Failure Or Chronic Kidney Disease (Ckd) At Hospital in Jember Regency - Fatarona , Anita; Kholifah , Nindi Nur (Journal of Nursing Periodic, 2024)
Introduction: Chronic kidney disease is one of the most important global health problems today related to mortality, with its prevalence significantly increasing every year worldwide. Chronic kidney failure occurs because the kidneys cannot maintain balance in the body. Decreased kidney function results in the kidneys not producing the hormone erythropoietin, which can cause a decrease in hemoglobin levels. Low hemoglobin levels can cause anemia in patients with chronic kidney failure. This study aimed to analyze the relationship between hemodialysis frequency and hemoglobin levels in chronic renal failure patients at hospital in Jember. Method: The study used analytical observational research with a cross-sectional design. The sample of this study amounted to 30 respondents using consecutive sampling. Data collection using observation sheets. Results: Chronic renal failure patients undergoing hemodialysis 2 times a week (73.3%)in the always category and hemoglobin levels in the low category (76.7%). With a percentage of p-value results of 0.002 where p<α (0.002<0.005). Conclusion: There is a relationship between hemodialysis frequency and hemoglobin levels in chronic renal failure patients at hospital in Jember.